P082 The functional anatomy of creativity does not involve the cerebellum. Issue 3 (March 2017) - Ferrucci, R.; Ruggiero, F.; Fumagalli, M.; Vergari, M.; Cortese, F.; Mameli, F.; Bocci, T.; Lavazza, A.; Priori, A.
Abstract : Introduction: Creativity is the ability to come up with new, original solutions to problems. There are two basic ways we can think about the possible solution. These two types of thinking are called divergent thinking, when multiple related ideas for a given topic or solutions to a problem are generated, and convergent thinking that involves finding the one "right" solution to a problem (Guilford, 1950 ). Though several brain areas are activated during creativity process, it is unknown whether and how subcortical structures are also involved (Jung et al., 2013 ). Objectives: We investigated whether convergent and divergent thinking can be modulated by cerebellar transcranial direct current stimulation (tDCS) (Ferrucci et al., 2014 ). Materials & methods: 15 healthy subjects (aged 25–30; 9 female and 6 male) were recruited. We delivered anodal cerebellar tDCS (2 mA, 20 min) ( n = 8) and sham tDCS ( n = 7). In each session, Remote Associates Task (RAT) was administered before (baseline T0) and after tDCS (T1) while Divergent Thinking Test (DTT) was administered during stimulation. Non parametric test was used to analize the data. Results: Anodal cerebellar tDCS and sham tDCS failed to induce significant changes in all tasks ([mean ± SEM] Anodal vs Sham: RAT 0.75 ± 0.64 vs 0.71 ± 0.86, p = 0.9; DDT 78.19 ± 2.13 vs 80.33 ± 5.9, p = 0.53). Conclusion: We did not observe creativity modulation with cerebellar tDCS. Because previous studies reported that hemispheric tDCS modulated creativity, we can conclude that the cerebellum in not involved in creativity at least in the task we tested.